The implementation of FMEA for analyzing the risk of natural disaster logistic activities (case study: CSER project childfund international) - Bombang, Serli (Operations Excellence: Journal of Applied Industrial Engineering, 2023)
Indonesia is a country prone to natural disasters due to its location at the convergence of active tectonic plates. During natural disasters, logistics becomes crucial in emergency response. The aim of this study is to analyze the risks involved in logistics activities during natural disaster emergency response, focusing on the case of Central Sulawesi in 2018. The method used in this research is Failure Mode and Effect Analysis (FMEA). This research is descriptive-exploratory in nature based on interviews and questionnaire distribution. The results indicate eighteen risks occurring during emergency response logistics activities conducted by Childfund International. Calculation results show six critical risks in emergency response logistics activities, namely errors in planning required demand, expired goods, expiration dates too close, closure or absence of goods reception, prolonged accountability report preparation process, and incomplete accountability reports